Innovative directions of aerospace construction development in the conditions of transformation - Chornodid, Ihor; Sarry, Vira; Fisunenko , Pavlo; Popovychenko, Iryna (Ways to Improve Construction Efficiency, 2022)
The article reveals the essence and main innovative directions of the development of aerospace construction in Ukraine in the conditions of transformation of the national economy. It is substantiated that the development of the industry should be based on the principles of an institutional and innovative approach aimed at increasing competitiveness, technological stability and efficiency of production processes. It is shown that aerospace construction is a key element of the strategic infrastructure of the state, which determines its defense capability, scientific and technical potential and ability to integrate into global high-tech markets. Particular attention is paid to the role of complex reconstruction, which is considered as a systemic mechanism for updating the material and technical base and transition to new technological systems. It is proven that the modernization of production and scientific facilities of the aerospace complex should be carried out on the basis of digitalization, energy efficiency, environmental friendliness and the introduction of intelligent management systems. The article substantiates that comprehensive reconstruction is not only an engineering and technical, but also a socio-economic process that ensures the restoration of infrastructure, increased employment and the development of an innovative environment. The significance of public-private partnership (PPP) in the implementation of reconstruction and innovation projects is determined. It is shown that PPP contributes to attracting investments, introducing advanced technologies, strengthening coordination between state structures, business and scientific institutions. For the aerospace complex, such a model of cooperation is critically important, as it allows for the simultaneous restoration of production capacities, modernization of infrastructure and development of dual technologies. The results of the study prove that innovation-oriented aerospace construction based on public-private partnership is a strategic direction of post-war reconstruction of Ukraine, which ensures sustainable development, strengthening of scientific and technical potential, increasing international competitiveness and technological autonomy of the state.